Status update of ISO TC67/SC8/WG5: Materials for arctic applications: - Hauge, M.; Maier, M.; Walters, C.L.; Ostby, E.; Kordonets, S.M.; Zanfir, C.; Osvoll, H. (2015)
An ISO subcommittee was set up in 2011 to improve the existing standards and norms with respect to arctic offshore operations for the petroleum, petrochemical, and natural gas industries. Within this subcommittee, a specific working group was established to address the application of materials in the environment of the arctic and cold regions. The work is focusing on a number of specific aspects related to the application of ferritic steels. The current paper summarizes the efforts of this working group to date